Review of Various Influential Factors in the Production of Robusta Coffee Effervescent Drink Tablets - Miftahul Wahidatun Ni’mah; Diah Dwi Lestari; Ayuni Rizma Maulida; Umar Hafidz Asy'ari Hasbullah (International Journal of Advance Tropical Food, 2021)
Coffee is one of Indonesia's leading plantation commodities, which is ranked third in the world. Currently, coffee-based drinks have become a lifestyle in the millennial era. The high interest in coffee affects the economy of the community. Various efforts were made to further encourage the level of coffee consumption, especially in the form of beverages. On the other hand, it is necessary to diversify the product by highlighting the technology side, such as making effervescent which is easier, more practical, and can be enjoyed directly with cold water. Effervescent is known as a product that can cause gas bubbles as a result of the reaction of acids and bases when dissolved in water. The resulting gas bubbles are carbon dioxide which gives a sparkling effect (a taste sensation like sparkling water). The use of coffee as an effervescent raw material is related to its taste, bioactive compounds, and antioxidants. Coffee extract powder can be made from robusta and arabica coffee roasted at medium level with low-temperature crystallization, spray drying, freeze drying, and vacuum drying. Other materials that need to be added such as acid sources, bases, fillers, and binders can affect the effervescent characteristics such as tablet hardness, moisture content, hygroscopicity, and dissolution time. The recommended composition is citric acid, sodium bicarbonate, dextrin, and PVP (Polyvinilpyrrolydone).